MARKETPLACE SYSTEM DESIGN FOR COMMUNICATION PLATFORM IN RURAL AREA - Andika Ramadhan, Febbry
The internet still cannot be used by all residents in Indonesia. 96.7 million people in Indonesia have not used the internet, most of them are people in rural areas. This condition can be utilized to improve the economy of people in rural areas, namely by providing the internet with marketplace facilities for the area. The marketplace is one of the most accessed websites in Indonesia in 2019. Therefore, this final project will discuss the creation of a marketplace website system for rural areas by utilizing a communication platform. The purpose of this final project is to design a marketplace website system that can conduct purchasing, barter, and selling transactions for rural areas and implement the results of the marketplace website system design. Marketplace websites are created using HTML, CSS, JavaScript, and PHP programming languages and use MySQL as a database. The website is named Belanja which is a marketplace website that can carry out purchasing, barter, and selling agricultural products.